Spatial distribution of two maternal messengers in Paracentrotus lividus during oogenesis and embryogenesis. - Di Carlo, M (1994)
We demonstrated that two mRNAs that are synthesized during the vitellogenic period of oogenesis and that code for cell surface proteins are asymmetrically distributed in the unfertilized egg of Paracentrotus lividus. At fertilization, these RNAs rapidly localize in the cortical zone at the animal pole of the egg. They are then detected in the mesomeres and the macromeres, but not in the micromeres, and thereafter are found in the ectoderm but not in the vegetal plate, mesenchyme cells, or early intestine. They disappear in late gastrula. The proteins synthesized by these mRNAs show the same territorial location during the period examined here, which included the unfertilized egg and the 16-blastomere stage. These conclusions were reached on the basis of in situ hybridization and immunostaining experiments, as well as Northern and Western blot analyses of isolated blastomeres. The possible significance of this asymmetric distribution of these two mRNAs and proteins in the establishment of the animal/vegetal axis is discussed.